A comparative study of low-cost coating processes for green & sustainable organic solar cell active layer manufacturing - Varun, Vohra; Nur Tahirah, Razali; Rafeah, Wahi; Lucia, Ganzer; Tersilla, Virgili (Elsevier, 2021)
Owing to their facile integration into existing commercial products, high volume manufacturing of organic solar cells (OSCs) can be expected in the upcoming years. Therefore, it is important to evaluate the performance and sustainability of various active layer coating methods for OSCs. Herein, we compare four active layer coating processes: spin-coating, blade-coating, spray-coating and push-coating for poly(2,7-carbazole-alt-dithienylbenzothiadiazole):[6,6]-Phenyl-C71-butyric acid methyl ester (PCDTBT:PC71BM) active layers deposition. The optical, morphological and photovoltaic parameters of the active layers are studied. The suitability of each coating method for industrial manufacturing of PCDTBT:PC71BM OSCs is discussed in terms of environmental impact, necessary investments and running costs. Our results confirm that, despite producing high quality and high performance OSCs, spin-coating is unsuitable for high volume manufacturing due to the large amounts of materials and hazardous solvents wasted in the process. Blade-coating provides a good balance between low running costs, low environmental impact and decent performances but the process introduces lateral compositional gradients which could be detrimental for large area OSC processing. Spray-coating requires minimal initial investments but has relatively low performance and low manufacturing sustainability. Push-coating yields OSCs which perform as well as spin-coated ones, with a much lower environmental impact and cost. We should thus look forward to seeing whether this green and sustainable technology can develop into a large area coating process in the future.